Penerapan Metode Tutor Sebaya Dalam Meningkatkan Bacaan AL-Qur'an Siswa di Mts Darul Ihsan - eva yuliza; Ali Wardana; Zulfia Siskawati (STAI Hubbulwathan Duri, 2019)
AbstractHow to deliver material by the teacher to students at MTs Darul Ihsan. The ability to read for all students is the spearhead or basic ability that must be possessed by all students, by being able to read well and fluently can make it easier for students to understand each lesson item or material delivered by the teacher, by not being able to read well, it can complicate students in understanding the contents of the subject matter. A number of things happened at MTs Darul Ihsan if they were allowed to continue. The results of the application of the peer tutoring method in improving the reading of the Koran of students at MTs Darul Ihsan. The application of learning using the peer tutoring method can improve the reading of Al-Qur'an at MTs Darul Ihsan class VII.